The effect of the noncentral impurity-matrix interaction upon the thermal expansion and polyamorphism of solid CO-C60 solutions at low temperatures - Dolbin, A.V.; Esel’son, V.B.; Gavrilko, V.G.; Manzhelii, V.G.; Vinnikov, N.A.; Gadd, G.E.; Moricca, S.; Cassidy, D.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Orientational glasses with CO molecules occupying 26 and 90% of the octahedral interstitial sites in the C60 lattice have been investigated by the dilatometric method in a temperature interval of 2.5–22 K. At temperatures 4–6 K the glasses undergo a first-order phase transition which is evident from the hysteresis of the thermal expansion and the maxima in the temperature dependences of the linear thermal expansion coefficientsa(T), and the thermalization times t1(T) of the samples. The effect of the noncentral CO–C60 interaction upon the thermal expansion and the phase transition in these glasses was clarified by comparing the behavior of the properties of the CO–C60 and N2–C60 solutions.